Antibiotic use among hospitalized patients in northern Nigeria: a multicenter point- prevalence survey - Abubakar, Usman (2020)
Abstract Background: The evaluation of antibiotic use among hospitalized patients is a primary step required to design antibiotic stewardship intervention. There is paucity of data describing antibiotic use in hospitals across Northern Nigeria. This study evaluates the prevalence and indications for antibiotic use among inpatients in three acute care hospitals. Methods: A point-prevalence survey was conducted among patients in the wards before or at 8.00 a.m. on the day of the survey, using the point-prevalence survey of healthcare-associated infections and antimicrobial use in European acute care hospitals protocol. The survey was conducted between April and May 2019. The medical records of the patients were reviewed by a clinical pharmacist with the support of physicians and nurses. Results: Overall, 80.1% (257/321) of the patients used at least one antibiotic on the day of the survey. The prevalence of antibiotic use ranged from 72.9% in obstetrics and gynecology to 94.6% in pediatric medical specialty. Community acquired infections (38.7%) and surgical antibiotic prophylaxis (22.5%) were the most common indications. Surgical antibiotic prophylaxis was used or scheduled to be used for more than a day in all the cases. Metronidazole (30.5%), ciprofloxacin (17.1%), ceftriaxone (16.8%), amoxicillin-clavulanate (12.5%) and gentamicin (11.8%) were the most commonly prescribed antibiotics. Overall, broad spectrum antibiotics represented one-third of all the prescriptions. The change of initial antibiotic prescription was reported in one-third of the patients and the reasons include a switch to oral antibiotic (28.5%), escalation (4.5%) and de-escalation (3.6%). Of the 257 patients with an antibiotic prescription, 6.2% had redundant antibiotic combinations. Conclusion: The prevalence of antibiotic use was high with one in three prescriptions having a broad spectrum antibiotic. Prolonged use of surgical antibiotic prophylaxis and redundant antibiotic combination were observed. Antimicrobial stewardship interventions are recommended in order to reduce the use of antibiotics and promote appropriate antibiotics prescribing